On the Informational Size of Message Spaces for Efficient Resource Allocation Processes - Chander, Parkash (Econometrica, 1983)
[This paper develops a framework of analysis for studying the informational properties of a certain class of "parametric" resource allocation processes. It is shown that the Taylor process (related to certain ideas for planning in the so-called socialist economies as put forward by Taylor [126] is informationally efficient in the sense that any informationally decentralized resource allocation process which has similar (static) properties (Pareto optimality) must use a message space which is dimensionally at least as large as that of the Taylor process. We also show that in general greater informational decentralization can be achieved through parametric than through "nonparametric" processes.]